Systematic notes on Cryptoperla Needham, 1909 (Plecoptera: Peltoperlidae) from China, with description of a new species from Zhejiang Province - Chen, Zhi-Teng (Zootaxa, 2020)
A new species of the peltoperlid genus Cryptoperla Needham, 1909, C. zhejiangensis sp. nov. from Zhejiang Province of southeastern China is described, the first representative of the genus known from the province. Males of the new species are characterized by the cerci with an unmodified first segment and with the longest bristles on segments 5–8, and by the aedeagus with two large apical lobes and six smaller median lobes. The large rounded subgenital plate covering the entire sternum 9 but not exceeding half-length of sternum 10 distinguishes the female of the new species. Two species groups, the C. formosana group and the C. japonica group are proposed to accommodate the currently known Cryptoperla species. The type localities of all Chinese Cryptoperla species are updated.